Bottom-up construction of chiral metal-peptide assemblies from metal cluster motifs - Pei-Ming Cheng; Tao Jia; Chong-Yang Li; Ming-Qiang Qi; Ming-Hao Du; Hai-Feng Su; Qing-Fu Sun; La-Sheng Long; Lan-Sun Zheng; Xiang-Jian Kong (Nature Communications)
Abstract The exploration of artificial metal-peptide assemblies (MPAs) is one of the most exciting fields because of their great potential for simulating the dynamics and functionality of natural proteins. However, unfavorable enthalpy changes make forming discrete complexes with large and adaptable cavities from flexible peptide ligands challenging. Here, we present a strategy integrating metal-cluster building blocks and peptides to create chiral metal-peptide assemblies and get a family of enantiopure [R-/S-Ni3L2]n (n = 2, 3, 6) MPAs, including the R-/S-Ni6L4 capsule, the S-Ni9L6 trigonal prism, and the R-/S-Ni18L12 octahedron cage. X-ray crystallography shows MPA formation reactions are highly solvent-condition-dependent, resulting in significant changes in ligand conformation and discrete cavity sizes. Moreover, we demonstrate that a structure transformation from Ni18L12 to Ni9L6 in the presence of benzopyrone molecules depends on the peptide conformational selection in crystallization. This work reveals that a metal-cluster building block approach enables facile bottom-up construction of artificial metal-peptide assemblies.